Cataract incidence after total-body irradiation - Zierhut, Dietmar; Lohr, Frank; Schraube, Peter; Huber, Peter; Wenz, Frederik; Haas, Rainer; Fehrentz, Dieter; Flentje, Michael; Hunstein, Werner; Wannenmacher, Michael (International journal of radiation oncology, biology, physics, 2000)
Purpose: The aim of this retrospective study was to evaluate cataract incidence in a homogeneously-treated group of patients after total-body irradiation (TBI) followed by autologous bone marrow transplantation or peripheral blood stem cell transplantation. Methods and Materials: Between 1982 and 1994, a total of 260 patients received either autologous bone marrow or blood stem cell transplantation for hematological malignancy at the University of Heidelberg. Two hundred nine of these patients received TBI in our hospital. Radiotherapy was applied as hyperfractionated TBI, with a median dose of 14.4 Gy in 12 fractions over 4 days. Minimum time between fractions was 4 h. Photons with an energy of 23 MeV were used with a dose rate of 7-18 cGy/min. Ninety-six of the 209 irradiated patients were still alive in 1996; 86 of these patients (52 men, 33 women) answered a questionnaire and could be examined ophthalmologically. The median age at time of TBI was 38.5 years, with a range of 15-59 years. Results: The median follow-up is now 5.8 years, with a range of 1.7-13 years. Cataract occurred in 28/85 patients (32.9%) after a median of 47 months (1-104 months). In 6 of 28 patients who developed a cataract, surgery of the cataract was performed. Whole-brain irradiation prior to TBI had been performed more often in the group of patients developing cataract (14.3%) versus 10.7% in the group of patients without cataract. However, there was no statistical difference (Chi-square, p > 0.05). Conclusion: Cataract is a common side effect of TBI. Cataract incidence found in our patients is comparable to results of other centers using a fractionated regimen for TBI. To assess the incidence of cataract after TBI, a long-term follow-up is required.